PENDIDIKAN KARAKTER DALAM AL-QUR’AN KAJIAN ATAS TAFSIR AL-IBRIZ KARYA BISRI MUSTOFA - Munawar, Munawar; Zuhri , Saifudin; Surasman , Otong (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2023)
This study discusses his work, Bisri Mustofa, Tafsir Al-Ibriz, which raises the concept of character education with an emphasis on ethical and moral values and upholding virtue values in everyday life. The concept of character education contained in Tafsir Al-Ibriz includes the following main points: First Spiritual Values: Bisri Mustafa stressed the importance of connection with God in shaping character. Faith, piety, and humility are the main foundations in this view. Both Ethics and Morals: Tafsir Al-Ibriz teaches the importance of good and honest behavior in all aspects of life. Bisri Mustofa emphasizes honesty, compassion, and hard work as the main components of character education. Third Self-Development: This work highlights the importance of personal effort in developing character. Self-discipline, courage, and self-control are the elements emphasized. The Importance of Education: Bisri Mustofa pointed out that education has a crucial role in shaping the character of the younger generation. Education that is not only focused on academic aspects, but also moral, emotional, and spiritual development. Fourth, Relevance to the Young Generation: The view of character education according to Bisri Mustofa in Tafsir Al-Ibriz remains relevant to the character development of today's young generation. The modern era which is filled with moral and cultural challenges requires a strong foundation in the form of ethical values and virtues taught by Tafsir Al-Ibriz. This research is a qualitative research which in its preparation uses the literature review method. Based on the results of the study it can be concluded that the educational values of surah Luqman verses 12-19 in Tafsir Al-Ibriz broadly cover three things, namely aqidah education, sharia education, and moral or character education